Visualizing the vibration effect on the tandem-pulsed gas metal arc welding in the presence of surface tension active elements. (November 2020) - Hamed Zargari, H.; Ito, K.; Kumar, M.; Sharma, A.
Highlights: A novel simulation of the workpiece vibration assisted welding is developed. The creation mechanism of the finger-shaped penetration is modeled in TP-GMAW. The vibration effect on the penetration shape associated with the surface tension active elements is studied. Visualizing the 2D and 3D streamlines for tracing the material path in the weld pool. Abstract: In this study, a three-dimensional model of the tandem-pulsed gas metal arc welding process is simulated to investigate the heat transfer and material flow in the presence of vibration and the surface tension active elements. The simulation results are in agreement with optical microscopy images of weld cross-section obtained with different conditions, including with and without vibration-assisted welding. The material flow is visualized using 2D and 3D streamlines on the temperature contour maps. It is found that during the operation of pulsed welding, the heat follows a very stable pattern, although the fluid streams continuously change in the rear region of the weld pool, which is responsible for the final geometry of penetration. Consideration of the effect of surface tension active elements on the Marangoni force improves the simulation results noticeably. A novel approach addresses the effect of sulfur content that comes from both workpiece and filler material. Applying the vibration leads to lower heat input by affecting the free surface behavior and plays an important role in the penetration shape change.